Transformation approach to education of adults in modern conditions: global trends and challenges - Lazorko, Olha (Psychological Prospects Journal, 2019)
Rapid changes in information technologies are changing the structure of society. In the information society, information is the main force and source of capital. In such a period, the production and use of real information are essential. One of the characteristics of an information society is a person who is capable of learning. Within the information society, the individual must understand, interpret and use scientific data; develop new skills and have the ability to solve problems. The most urgent challenge of today is the ability to prepare both the individual and society for the future to compete with the changes themselves. The integration of the individual into the fast-changing information society and the search for the place it deserves in this society, the acquisition of new information and the enrichment of opportunities is made possible through life-long learning. A lifelong learner updates his life perspective, behaviour and values. The social purpose and responsibility of education for a new information society are now increasingly under the scrutiny of academics, business and political institutions.Increasing life expectancy and decreasing fertility, reducing early retirement and extending the working life of workers have become significant goals of the world social policy agenda. In this context, the adaptability and efficiency of the existing workforce have become an important issue. The purpose of this article is to review reference research and statistics on global labour market trends and the latest forms of adult education and training. The review covers English-language literature of the last two decades.